PARTISIPASI MASYARAKAT DALAM PENGELOLAAN KAWASAN KOTA LAMA SEMARANG - Togu Exaudi Mangihut; Parfi Khadiyanto (Jurusan Perencanaan Wilayah dan Kota, 2014)
Abstrak: Setiap kota memiliki kawasan bersejarah, salah satunya kawasan kota lama di Semarang. Kawasan kota lama sebenarnya merupakan pusat kota Semarang jaman kolonial, dimana tampak berbagai bangunan pemerintahan dan sejumlah bangunan pendukung lain sebagai unsur kawasan pusat kota dengan gaya arsitektur Belanda. Seiring dengan perkembangan Kota Semarang, telah terjadi penurunan akibat pergeseran fungsi pada Kota Semarang. Kawasan kota lama Semarang sebagian besar dikelola oleh pemerintah, sementara keterlibatan masyarakat sangatlah terbatas. Partisipasi masyarakat dalam upaya pelestarian warisan budaya merupakan salah satu prioritas yang harus tercapai dalam setiap kegiatan pemanfaatan benda cagar budaya yang berwawasan pelestarian, oleh karena itu perlu kiranya diteliti bagaimana partisipasi masyarakat dalam pengelolaan kawasan Kota Lama Semarang selama ini. Berdasarkan hasil penelitian, salah satu bentuk partisipasi masyarakat dalam upaya pengelolaan Kota Lama Semarang yaitu dengan memberikan sumbangan tenaga berupa kerja bakti. Selain itu, mereka juga mengadakan pertemuan warga yang dilakukan satu kali dalam sebulan, yang dihadiri oleh sebagian warga untuk tingkat RW dan seluruh warga untuk tingkat RT. Dalam hal ini tingkat RT cenderung berbentuk partisipasi langsung sedangkan tingkat RW berbentuk partisipasi tak langsung. Tingkat partisipasi masyarakat yang terjadi di kawasan kota lama menurut Arnstein dapat digolongkan pada tingkat informing dan consultation. Usulan bagi upaya peningkatan partisipasi masyarakat di kawasan kota lama adalah perlunya peningkatan sumber daya manusia melalui kegiatan penyuluhan dan pembinaan tentang manfaat pentingnya pengelolaan kota lama itu sendiri. Selain itu, pemerintah juga diharapkan memberikan arahan dan dukungan dengan pengawasan pengelolaan Kota Lama Semarang.Kata Kunci : Partisipasi masyarakat, kegiatan pengelolaan, kota lama Semarang Abstract: Every town has a historic district , one of which the old town area in Semarang. Old town area is actually an original Semarang city center , which looks various government buildings and a number of other ancillary buildings as elements of the downtown area with the Dutch architectural style. Along with the development of the city, there has been a decline. Due to a shift in the function of the Old City of Semarang. The old town area of Semarang which in the past was the center of the city and the main structure of the region, now no more as a city to die of concern. The old town area of Semarang is largely managed by the Government, while community involvement is extremely limited. Public participation in the preservation of cultural heritage is one of the priorities which must be achieved in each of the activities of cultural heritage objects that utilization of insightful preservation, therefore needs to be examined how public participation in the management of the old city of Semarang. According to the observation result, one of the forms of community participation is by giving voluntary labor service. They were also organize community meetings held once every month, which attended by a part of the community on village level and all of the community on neighbouring level. Within this neighbouring level the participations tend to be the direct one, meanwhile, in the village level are tends to be an indirect participation. The communities are willing to carry out the activities without any force. According to Arnstein category, the participation level in the Old City of Semarang can be grouped on informing or giving information level and consultation. The suggestions for the improvement of community participation within management of the old city effort in the old city of Semarang is the necessity of improving human resources and public awareness, by providing elucidation and building activities concerning the importance of benefit from management of the old city. In addition, the local government is also expected to give more aspiration in giving directions and to support the community, by mending the planning management and supervising the management of the old city.Keyword : public participation, the management of the old city, the Old City of Semarang